Indonesia’s Mangosteen Export Risk Management Strategy to China - Ayu, Sri Fajar; Situmorang, Patricia Srisere Ikaria (Universitas Panji Sakti, 2025)
Indonesia is one of the leading global producers of mangosteen, with China absorbing over 70% of its export volume. Despite this, Indonesia’s market share remains limited compared to its competitors, such as Thailand. This study examines the short- and long-term relationships between key macroeconomic variables—mangosteen export price (HEC), export value (NE), Yuan to USD exchange rate (NTC), Rupiah to USD exchange rate (NTI), Indonesia’s real exchange rate (NTR), and export volume (VE)—and the performance of exports to China using the Vector Error Correction Model (VECM), which is appropriate for examining both long-run equilibrium (cointegration) and short-run dynamics among the macroeconomic variables. The model captures cointegration, causal interactions, impulse responses, and variance decomposition. Findings indicate that, in the long run, NTC, NTI, NTR, and VE have a significant influence on export prices, while no statistically significant short-run causality is observed. Key risks identified include exchange rate volatility, over-reliance on the Chinese market, price fluctuations, high logistics costs, and inconsistent product quality. To mitigate these issues, the study recommends exchange rate stabilization, export market diversification, investment in cold chain logistics, and the adoption of Good Agricultural Practices (GAP) with digital traceability systems. The findings support the formulation of evidence-based policies to strengthen the global competitiveness of Indonesia’s horticultural exports.